Three new Neotropical genera of Odiniidae (Diptera: Acalyptratae) - Gaimari, Stephen D. (Zootaxa, 2007)
Three new genera of Odiniidae (Diptera) are described from Costa Rica, including Helgreelia gen. nov. (type species, albeto sp. nov.; additional species, parkeri sp. nov.) and the monotypic genera Neoschildomyia gen. nov. (type species, fusca sp. nov.) and Pradomyia gen. nov. (type species, hadromera sp. nov.). A key to the New World genera of the family is provided.